Occurrence of aflatoxin M1 and its main determinants in raw cow milk the Chiriquí in Panama farms - Vega, Aracelly (2025)
Introduction: Aflatoxin contamination and its effects on human health have been a global concern and a research subject in developed countries for many decades. However, data generated from Latin America are scarce. Objective. To evaluate the occurrence of aflatoxin M1 (AFM1) and to identify its determinants in raw cow milk under current farm feeding practices in Panama. Materials and Methods. The study included 32 raw milk samples and 79 dairy cattle feed samples from 32 farms suppliers for a Panama dairy processing company. Contents of aflatoxin B1 (AFB1) and AFM1 were determined using HPLC-FLC and immunoaffinity columns. The carry-over of AFB1 to AFM1 was determined according to aflatoxin contents in feed and raw milk. A survey was also applied to all dairy farmers in the study regarding the explanatory variables associated with AFM1 occurrence in milk. Results. The overall prevalence of AFB1 in feeds was 39.2%, whereas the highest prevalence was for concentrate feed (74.3%) and the lowest (3.70%) for fresh forages. The occurrence of AFM1 in milk was 46.8%. The carry-over from AFB1 to AFM1 averaged 2.36%, which is characteristic of low-producing cows. Conclusion. The incidence and concentration of AFB1 in dairy cattle feed observed in the present study resulted under the maximum levels set by the U.S. Food and Drug Administration (FDA) and the European Union Commission Regulation (EC). Under current feeding practices, silage and haylage fed are determinants of AFM1 occurrence in tropical raw cow milk.